Análise de transformações de fases nas ligas Ti-35Nb-7Zr e Ti-xNb-3Fe por espectroscopia mecânica - Muñoz Chaves, Javier Andres (2013)
In recent decades the study of β-Titanium alloys are attracting the interest to the biomaterials science community in general, since have improved properties as compared with current commercial biomedical alloys which present problems of both mechanical and chemical compatibility. In this sense, the determination and optimization of the mechanical properties, in particular of the elastic modulus, through of control the phases present that are of great importance. In this study was determined the dynamic elastic modulus (E), their relative variation ( ΔE/E) and internal friction (Q-1) as function of temperature by mechanical spectroscopy technique, being that the information provided by these parameters, associated with complementary characterization techniques and theoretical parameters of the literature provided relevant information on the phases stability in some alloys of the Ti-Nb-Zr and Ti- Nb-systems. Thus, complex anelastic relaxation processes were observed which through cyclic heat treatment and aging was possible to dissociate into their component of phase transformations, which highlighted in the temperature range between 300 K and 700 K the sequence β → β + ω → β + ω + α → β + α, and once these transformations are developed, in a joint manner are also present relaxation processes that include interactions of elements containing alloys with interstitial atoms. At low temperature (130 K-300 K), a process of relaxation was observed, which may be related to processes such as β → ω (athermic) transformation and/or H-O interactions. However by the behavior of the elastic modulus this process may be linked in part to the reverse martensitic transformation β→α" being possible to identify Ms and Af temperatures. In addition was characterized a low modulus of elasticity, yielding values between 67 and 54 GPa, which are related to the greater stability of the β phase, being these suitable values regarding the mechanical compatibility as compared with commercial alloys used as biomaterials.